For three vectors u, v and w show that:

(u×v).[(v×w)×(w×u)]= [u.(v×w)]^2 .

You have probably already seen that

Ax(wxu) = w(A.u)-u(A.w)
Now let A = vxw
Then
(vxw)x(wxu) = w(uxvxw)
So,
(uxv).(vxw)x(wxu) = (uxv).w(u.vxw)
= (uxv.w)(u.vxw)
= (u.vxw)^2

There are other proofs online

To show that (u×v).[(v×w)×(w×u)]= [u.(v×w)]^2, we can use properties of the dot product and cross product of vectors.

Let's break it down step-by-step:

Step 1: Expand the expression (v×w)×(w×u):
(v×w)×(w×u) = [(v×w) dot (w×u)] - [(v×w) dot (w×u)]

Step 2: Simplify the dot products between the cross products:
[(v×w) dot (w×u)] - [(v×w) dot (w×u)]
= [(v dot (w×u)) dot (w×u)] - [(w×u) dot (v×w)]

Step 3: Simplify the dot products:
= [(v dot w) dot u] - [(w×u) dot (v×w)]
= (v dot w) dot u - (w×u) dot (v×w)

Step 4: Rewrite the dot products between the cross products:
(v dot w) dot u - (w×u) dot (v×w)
= (v dot w) dot u - (w dot (v×w)) dot u

Step 5: Simplify the dot product between w and (v×w):
(w dot (v×w)) dot u = 0

Step 6: Simplify further:
(v dot w) dot u - (w dot (v×w)) dot u
= (v dot w) dot u - 0 dot u
= (v dot w) dot u

Step 7: Rewrite (v dot w) as [u.(v×w)]
(v dot w) dot u
= [u.(v×w)] dot u
= u dot [u.(v×w)]
= [u.(v×w)]^2

Therefore, (u×v).[(v×w)×(w×u)] is equal to [u.(v×w)]^2, as required.

To show that (u×v).[(v×w)×(w×u)] = [u.(v×w)]^2, we can use the properties of the dot product and the cross product.

Let's start by expanding the left-hand side (LHS) of the equation:

LHS: (u×v).[(v×w)×(w×u)]

First, let's compute the cross products:
v×w = |v||w|sin θ1 n1, where |v| and |w| are the magnitudes of vectors v and w, θ1 is the angle between v and w, and n1 is the unit vector perpendicular to the plane formed by v and w.

w×u = |w||u|sin θ2 n2, where |w| and |u| are the magnitudes of vectors w and u, θ2 is the angle between w and u, and n2 is the unit vector perpendicular to the plane formed by w and u.

Notice that (v×w)×(w×u) is a vector triple product. We can expand it using the properties of the cross product:

(v×w)×(w×u) = [(v×w)·(w×u)] - (v×w)(w×u)

Now, let's compute the dot product:
(v×w)·(w×u) = |v×w||w×u|cos θ3, where θ3 is the angle between v×w and w×u. Notice that the dot product of two cross products is equal to the product of their magnitudes and the cosine of the angle between them.

Substituting the cross products and the dot product back into the expression, we have:
LHS = (u×v).[(v×w)×(w×u)]
= (u×v).[[(v×w)·(w×u)] - (v×w)(w×u)]

Next, let's simplify the expression using the properties of the dot product and cross product.
First, we can expand the dot product:

LHS = (u×v).[(v×w)·(w×u)] - (u×v).[(v×w)(w×u)]

Notice that (u×v)·(v×w) = 0, since the cross product of two parallel vectors is always orthogonal (perpendicular) to both vectors. Therefore, the first term [(v×w)·(w×u)] equals zero.

LHS = - (u×v).[(v×w)(w×u)]

Now, we can use the properties of the triple vector product to simplify the remaining expression. In particular, we can use the fact that (v×w)(w×u) = (w·w)(v×v) - (v·w)(w×v).

LHS = - (u×v).[(w·w)(v×v) - (v·w)(w×v)]

Next, let's compute the dot product (w·w) and simplify the equation:
(w·w) = |w|^2 = w^2

LHS = - (u×v).[(w^2)(v×v) - (v·w)(w×v)]
= - (u×v).[w^2(v×v) - (v·w)(w×v)]

Now, let's compute the cross product (v×v) and simplify further:
(v×v) = |v||v|sin θ4 n4 = 0, since the sine of the angle between two parallel vectors is zero.

Therefore, (v×v) = 0.

With this, the expression can be simplified to:
LHS = - (u×v).[w^2(0) - (v·w)(w×v)]
= - (u×v).[- (v·w)(w×v)]
= (u×v).(v·w)(w×v)

Now, let's work on the right-hand side (RHS) of the equation:

RHS: [u.(v×w)]^2

First, let's compute the cross product (v×w) and take its dot product with vector u:

u.(v×w) = |u||v×w|cos θ5, where θ5 is the angle between u and v×w.

Next, let's square the expression:
[u.(v×w)]^2 = u^2 |v×w|^2 cos^2 θ5

Now, let's simplify the expression by substituting the magnitude of the cross product:
[u.(v×w)]^2 = u^2 (|v||w|sin θ1)^2 cos^2 θ5

Finally, we can simplify further by replacing |v||w|sin θ1 with |v×w|:
[u.(v×w)]^2 = u^2 (|v×w|)^2 cos^2 θ5

Comparing the RHS with the LHS, we can see that they are equal if cos^2 θ5 = 1 and (u×v).(v·w)(w×v) = u^2 (|v×w|)^2 cos^2 θ5.

Since cos^2 θ5 = 1, the RHS and LHS are equal when:

(u×v).(v·w)(w×v) = u^2 (|v×w|)^2

Thus, we have shown that (u×v).[(v×w)×(w×u)] = [u.(v×w)]^2.